Simultaneous determination of nineteen azo dyes in water samples by gas chromatography-mass spectrometry after Fe3O4@COF based dispersive solid phase extraction - Karlidag, Nazime Ebrar; Bodur, Sezin Erarpat; Gunkara, Omer Tahir; Bakirdere, Sezgin (NATURE PORTFOLIO, 2024)
This study was performed for the determination of nineteen azo dyes at trace levels in stream water sample by gas chromatography-mass spectrometry (GC-MS). The selected analytes were preconcentrated with the help of dispersive solid phase extraction (DSPE). Fe3O4 magnetic nanoparticle was modified with covalent organic framework (COF) and the synthesized Fe3O4@COF nanocomposite was used as adsorbent for the separation of the analytes from aqueous solution. The synthesized Fe3O4@COF was introduced to the literature for the first time in this study. Five different parameters (pH, volume of buffer solution, volume of desorption solvent, mixing period and amount of adsorbent) were univariately optimized to acquire high extraction outputs for each analyte. Under the optimum Fe3O4@COF-DSPE-GC-MS conditions, limit of detection (LOD), limit of quantitation (LOQ), linear range (LR), coefficient of determination (R2) and percent relative standard deviation (%RSD) were calculated using external calibration plots belonging to each analyte. LOD values were found between 2.8 and 70.7 mu g/kg with corresponding LOQ values ranging between 9.5 and 235.7 mu g/kg. In addition, %RSD values were lower than 12.8%. Matrix matching calibration method was used in spiking experiments. Percent recovery results obtained for spiked stream water samples were between 83.1 and 122.4%, with %RSD <= 17.5. The high percent recoveries confirmed the accuracy and applicability of the developed Fe3O4@COF-DSPE-GC-MS method for stream water samples.
Keywords: Azo dyes; Dispersive solid phase extraction; Magnetic organic framework; Gas chromatography-mass spectrometry; Water sample; LIQUID-LIQUID-EXTRACTION; GRAPHENE; NANOPARTICLES; PRECONCENTRATION; MICROEXTRACTION; ADSORBENT; ION; Science & Technology - Other Topics